2005
DOI: 10.1111/j.1944-9720.2005.tb02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Blogosphere: Use of Web Logs in the Foreign Language Classroom

Abstract: The words blog, blogger, blogging, and blogosphere have entered online technological dictionaries in the last decade. Recently, these personal electronic journals have received more attention and their increased popularity has led to their regular use in many different settings including the news, the political arena, and even in education. This article offers an overview of this relatively new technological tool, which serves as a form of micropublishing, and then discusses its potential uses in language clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 5 publications
4
76
0
6
Order By: Relevance
“…Also, blogging can enhance collaboration (Freeman & Brett, 2012;Godwin-Jones, 2003) though outliers might have existed among the participants (mean=3.661, SD=.701). Moreover, blogging can enable L2 learners to learn in an interactive manner (Ducate & Lomicka, 2005;Miceli, et al, 2010). Such affordances of blogging were also recognized by the interviewees as follows:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, blogging can enhance collaboration (Freeman & Brett, 2012;Godwin-Jones, 2003) though outliers might have existed among the participants (mean=3.661, SD=.701). Moreover, blogging can enable L2 learners to learn in an interactive manner (Ducate & Lomicka, 2005;Miceli, et al, 2010). Such affordances of blogging were also recognized by the interviewees as follows:…”
Section: Resultsmentioning
confidence: 99%
“…In language learning and teaching, previous research demonstrated that blogging can promote interaction (Ducate & Lomicka, 2005;Miceli, Murray, & Kennedy, 2010;Trajtemberg & Yiakoumetti, 2011). Also, it can lend support to L2 learning in terms of enabling students to learn autonomously and collaboratively (Amir, Ismail, & Hussin, 2011;Baggetun and Wasson, 2006;Bhattacharya & Chauhan, 2010;Bakar, 2009;Godwin-Jones, 2003;Warlick, 2005), and to be motivated (Amir, et al, 2011;Bakar & Ismail, 2009), as well as to develop learner confidence (Bakar, 2009;Bakar, Latif, & Ya'acob, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A further project reported by Ducate & Lomicka (2005) aimed to foster intercultural awareness. It accompanied a spring break trip of American students of French to France and a return visit of the French students to the USA a few weeks later.…”
Section: Blogs As a Tool For Teaching And Learningmentioning
confidence: 99%
“…Moreover, through exposure to a multitude of opinions and through awareness of writing for a wider audience, blogs also foster critical thinking, because learners need to reflect on the possible reactions of others to their postings (Williams & Jacobs, 2004;Ovarec, 2003;Ducate & Lomicka, 2005).…”
Section: Blogs As a Tool For Teaching And Learningmentioning
confidence: 99%
“…The aforementioned characteristics of Web 2.0 technologies help explain why reports on the use of wikis and blogs 5 represent an emerging growth market in the economy of CALL research (e.g., Ducate & Lomicka, 2005;Kost, 2007;Thorne & Payne, 2005). Importantly, wikis and blogs are spaces in which students have the potential to move from the conventional epistemic stance of knowledge consumer to that of knowledge producer, and, in so doing, to shift also from mere participation in an educational community to contributive and co-constitutive roles in that community.…”
Section: Web 20 and L2 Learningmentioning
confidence: 99%